Automatic Wireless Nurse Caller - Sigit Widadi; Sultan Al Badrun Munir; Nishith Shahu; Irfan Ahmad; Israa Al Barazanchi (Universitas Muhammadiyah Yogyakarta, 2021)
The nurse caller device is used as a special communication device between the patient and the nurse within the hospital area as a means of speeding the nurse's time response in providing immediate care to the patient. The designed wireless-based nurse caller device made installation easier and neater. The remote used a Bluetooth module MH-10 connected to the ATMega8 microcontroller as the sender and receiver. The data process using a microcontroller ATMega8 produced characters on the LCD, turned on the LED, and activated the buzzer to call the nurse. The results of the test on the device showed that the farthest distance taken by the HM-10 Bluetooth module in the open area (outdoor) was about 45 meters, and the closed area (indoor) was about 20 meters.